PEMANFAATAN LIMBAH BAGLOG DAN PUPUK NPK PADA TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Purwanti, Yani; Hawayanti, Erni; Sulistiono, Achmat (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2020)
Waste can be used as organic material rich in lignin and cellulose which is expected to increase the efficiency of the use of NPK fertilizers and increase the growth and production of shallots. Like other organic fertilizers, oyster mushroom baglog waste is able to increase the physical, chemical and biological fertility of the soil. The application of organic fertilizer is expected to increase the efficiency of the use of NPK fertilizers. This research took place from May to July 2019 which was carried out on land owned by farmers on Jalan Sukarela, Lorong Mataram, Sukarami District, Palembang City, South Sumatra. The layout in the field is based on the Split-plot Design. with 9 treatment combinations with 3 replications so that there were 27 plots and 5 sample plants. As Main Plot: Baglog Waste Fertilizer (L): 15 tons/ha (L1), 20 tons/ha (L2) and 25 tons/ha (L3). As a sub-plot, NPK fertilizer (N): 100 kg/ha (N1), 150 kg/ha (N2), 200 kg/ha (N3). The results showed that the use of baglog waste fertilizer of 20 tons/ha was able to increase the efficiency of NPK fertilization by 100 kg/ha and produced the highest tuber weight per plot of 733.33 g or the equivalent of 3.67 tons/ha.